Myasthenia and related disorders of the neuromuscular junction. Issue 8 (14th June 2010) - Spillane, Jennifer; Beeson, David J; Kullmann, Dimitri M
Abstract : Our understanding of transmission at the neuromuscular junction has increased greatly in recent years. We now recognise a wide variety of autoimmune and genetic diseases that affect this specialised synapse, causing muscle weakness and fatigue. These disorders greatly affect quality of life and rarely can be fatal. Myasthenia gravis is the most common disorder and is most commonly caused by autoantibodies targeting postsynaptic acetylcholine receptors. Antibodies to muscle-specific kinase (MuSK) are detected in a variable proportion of the remainder. Treatment is symptomatic and immunomodulatory. Lambert–Eaton myasthenic syndrome is caused by antibodies to presynaptic calcium channels, and approximately 50% of cases are paraneoplastic, most often related to small cell carcinoma of the lung. Botulism is an acquired disorder caused by neurotoxins produced by Clostridium botulinum, impairing acetylcholine release into the synaptic cleft. In addition, several rare congenital myasthenic syndromes have been identified, caused by inherited defects in presynaptic, synaptic basal lamina and postsynaptic proteins necessary for neuromuscular transmission. This review focuses on recent advances in the diagnosis and treatment of these disorders.